2016
DOI: 10.1186/s13075-016-1128-5
|View full text |Cite
|
Sign up to set email alerts
|

A specific anti-citrullinated protein antibody profile identifies a group of rheumatoid arthritis patients with a toll-like receptor 4-mediated disease

Abstract: BackgroundIncreased expression of toll-like receptor 4 (TLR4) and its endogenous ligands, is characteristic of rheumatoid arthritis (RA) synovitis. In this study, we evaluated how these TLR4 ligands may drive pathogenic processes and whether the fine profiling of anti-citrullinated protein antibodies (ACPA) based on their target specificity might provide a simple means to predict therapeutic benefit when neutralizing TLR4 in this disease.MethodsThe capacity of RA synovial fluids (RASF) to stimulate cytokine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…Importantly, differentially evolved ACPAs observed at later time points formed ICs that more potently stimulated macrophage TNF production, highlighting the potential for an increased pathogenic role of these affinity-matured ACPAs. The level of TNF produced by IC stimulation of macrophages was reduced by TLR-4 blockade, thus demonstrating the potential of TLR-4 as a therapeutic target in RA, as has been suggested previously (16,17,48,49). Taken together, our findings demonstrate that affinity maturation plays a critical role in epitope spreading and generation of ACPAs that more potently drive macrophage TNF production in RA.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, differentially evolved ACPAs observed at later time points formed ICs that more potently stimulated macrophage TNF production, highlighting the potential for an increased pathogenic role of these affinity-matured ACPAs. The level of TNF produced by IC stimulation of macrophages was reduced by TLR-4 blockade, thus demonstrating the potential of TLR-4 as a therapeutic target in RA, as has been suggested previously (16,17,48,49). Taken together, our findings demonstrate that affinity maturation plays a critical role in epitope spreading and generation of ACPAs that more potently drive macrophage TNF production in RA.…”
Section: Discussionsupporting
confidence: 84%
“…In GCF, citrullinated peptides were detected in samples from patients with both PD and RA, but also in samples from patients with RA or PD alone, and in samples from healthy controls. A number of the citrullinated sites that we identified in this study have previously been identified in RA synovial tissue or fluid, and demonstrated to act as autoantigen epitopes, including R35 in fibrinogen α , R715 in α 2 ‐macroglobulin, R450 and R304 in vimentin, R93 in histone H2B type 2‐E , R4 in histone 2A , as well as R69 and R71 in vimentin . We also detected citrullinated peptides in GCF and periodontal tissues that have not been described as autoantigens in RA.…”
Section: Resultssupporting
confidence: 63%
“…Notably, a number of citrullinated residues that we detected in periodontal samples have previously been identified in synovial fluid from RA patients (R35 in fibrinogen α [32], R715 in α 2 ‐macroglobulin, R450 and R304 in vimentin, and R93 in histone H2B type 2‐E [33]). In addition, we detected peptides with citrullinated residues at position R4 in histone 2A as well as at positions R69 and R71 in vimentin, that are described as autoantibody targets in RA . Citrulline 71 in vimentin was also recently detected in lung tissue samples, including those from smokers and patients with chronic obstructive pulmonary disease .…”
Section: Discussionmentioning
confidence: 76%
“…NI-0101, an anti-TLR4 antibody, can inhibit TLR4 signaling by blocking TLR4 dimerization (Monnet et al, 2015). It could successfully block cytokine release ex vivo and in vivo, prevent LPS-induced flu-like symptoms (Monnet et al, 2017), and block synovial fluids-induced pro-inflammatory cytokine production in monocytes isolated from RA patients (Hatterer et al, 2016). 1A6, another TLR4-antibody, has shown to target TLR4 activation (Spiller et al, 2008), ameliorate inflammation, and prevent the disease progression in a mouse model of colitis and protect against microbial-induced septic shock in vivo (Lima et al, 2015).…”
Section: Antibodiesmentioning
confidence: 99%